Iron deficiency anemia and thrombosis risk in children—revisiting an old hypothesis - Kalff, Hannah; Cario, Holger; Holzhauer, Susanne (Frontiers in Pediatrics, 2022)
Iron deficiency anemia has a high prevalence in children and has repeatedly been implicated as a risk factor for arterial and venous thrombosis. As an effective therapy for iron deficiency anemia is available, understanding the association between this form of anemia and the potentially severe thrombosis phenotype is of major clinical interest. Recent findings shed light on pathophysiology of hypercoagulability resulting from iron-restricted erythropoiesis. Specifically, an animal model of induced iron deficiency allowed identifying multiple mechanisms, by which iron deficiency anemia results in increased thrombus formation and thrombus progression both in arterial and venous thrombosis. These findings complement and support conclusions derived from clinical data. The purpose of this mini review is to summarize current evidence on the association of iron deficiency anemia and thrombosis. We want to increase the awareness of iron deficiency as a risk factor for thrombosis in the pediatric population. We discuss how novel pathophysiological concepts can be translated into the clinical settings and suggest clinical studies on prevention and treatment strategies in high-risk patient groups.